Patronage and Humanist Literature in the Age of the Jagiellons : Court and Career in the Writings of Rudolf Agricola Junior, Valentin Eck, and Leonard Cox - Glomski, Jacqueline L., 1951- (Book collections on Project MUSE., 2007)
Every epoch has its artists, thinkers, and creators, and behind many of these people, there is a patron waiting in the wings. Patronage and Humanist Literature in the Age of the Jagiellons looks at the relationship between humanist scholars and their patrons in east central Europe during the early sixteenth century. It is the first study in English specifically to address literary patronage as it existed in this particular time and place. Drawing on the writings of three itinerant scholar-poets associated with the courts of Cracow, Buda, and Vienna, Jacqueline Glomski argues that, even while they supported the imperial pretensions of the Jagiellonian monarchs, the humanist scholars of east central Europe also created effective propaganda for themselves by representing their own role in the conferring of fame upon their patrons. Using a wide array of source material, from dedicatory letters to panegyric and political literature, Glomski describes how important patronage was to the scholar-poets, and analyzes the process by which conventions of Renaissance humanism spread across Europe. Patronage and Humanist Literature in the Age of the Jagiellons is an insightful historic account that is accessible to anyone interested in patronage at the time of the European Renaissance.